Sudan: Negotiating southern independence. High stakes in the talks on post-referendum arrangements - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2010)
In Sudan, all eyes are currently on the preparations for the referendum on southern independence, scheduled for 9 January 2011. The southern government and international actors are expecting a clear vote for independence. Most attention is currently focussed on disputes between the central and southern governments over the referendum itself. Meanwhile, negotiations are taking place behind the scenes on arrangements for the post-referendum era. These negotiations will have a decisive impact on the risk of violent conflict associated with southern secession. Deals could be based on existing interdependencies between the two sides, with external actors backing up such arrangements. Where there are no such interdependencies, external assistance can support compromises between the two sides. Possible instruments include conditional debt relief and a UN mission to monitor security arrangements. Regardless of the referendum's outcome, economic interdependencies provide opportunities for stable north-south relations
Keywords: 320